How effective Auditory-Verbal Therapy (AVT) is for building language development of children with cochlear implants? A systematic review. - Binos, Paris; Nirgianaki, Elina; Psillas, George K. (My University, 2021)
This systematic review was designed to investigate the effectiveness of Auditory-Verbal Therapy (AVT) based on research findings of the last ten years. The systematic review was designed based on PRISMA guidelines. Search terms were chosen based on the research question and used in a search on PubMed database. Last decade’s published peer-reviewed papers meeting inclusion criteria were reviewed based on. The results revealed AVT as an important clinical approach that improves young cochlear implant (CI) children to outperform peers in bilingual-bicultural pro-grams in receptive vocabulary and speech perception or at the least be at a similar level on speech, language and self-esteem. Other aspects related with voice seemed also benefited, placing young CIs in the normal range for receptive vocabulary development. Less improvement noted in the ar-ea of reading. AVT approach can positively assist infants develop spoken language and support full integration into mainstream society despite the limited evidence presented. This position is supported by research findings of young CIs comparable to their hearing peers. Overall studies suggest AVT as a positive clinical approach for spoken language of young CIs and provide evi-dence that there is no advantage for the use of other alternative communication models before or after CI.
Keywords: AVT; Cochlear implants; Speech; Language; Effectiveness